The Effectiveness of Acupressure at Points LI4, SP6, and PC6 in Reducing Menstrual Pain Among Students at Poltekkes Kemenkes Malang (Campus IV – Kediri Midwifery Program) - Suci Wulandari; Susanti Pratamaningtyas; LA. Wijayanti; Desy Dwi Cahyani (Jurnal Kebidanan Manna, 2026)
Background: Menstrual pain is a menstrual disorder characterized by abdominal cramps. Menstrual pain occurs in women of reproductive age with pain radiating to the back, as well as nausea and vomiting, headaches and diarrhea. Sufferers who experience menstrual pain are unable to carry out daily activities optimally. Menstrual pain can affect physical limitations and academic concentration. Objective: To determine the effectiveness of acupressure at points LI4, SP6 and PC6 on reducing menstrual pain. Method: The study design used a pre-experimental with a one-group pretest posttest method. From a population of 179 people, a sample of 65 people was obtained using a simple random sampling technique. The research instruments used a questionnaire sheet for general data and menstrual data, a WaLIDD (Working ability, Location, Intensity, Days of Pain, Dysmenorrhea) measurement sheet, a SOP sheet, and oil/body lotion. Data analysis used univariate and bivariate analysis with the Wilcoxon Signed Rank test. Results: The bivariate test results showed a significance of 0.001 < 0.05, which means that acupressure at LI4, SP6, and PC6 points is effective in reducing menstrual pain in female students of the Ministry of Health Polytechnic of Malang, Campus IV Midwifery, Kediri. Conclusion: Acupressure at LI4, SP6, and PC6 points is effective in reducing menstrual pain. Suggestion: Acupressure therapy at LI4, SP6, and PC6 points can be used as a non-pharmacological intervention that can be applied in health services to help reduce menstrual pain.